Analisis Pengaruh Kualitas Layanan Website Komisi Pemilihan Umum Provinsi Jawa Timur dengan menggunakan Metode WebQual 4.0 - Misbakhul Akbar; Aditya Rachmadi; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-Government is designed as a site of interaction between the Government with the people, so that the public people is an important part in the functioning of E-Government. Public poeple satisfaction with KPU Jatim website is important for the realization of good E-Government This study aims to determine the influence of website quality on user satisfaction using multiple linear regression statistik and the WebQual 4.0 method consisting of Usability, Information Quality, and Service Interaction Quality. From 3570 population, got 97 sample minimum based on calculation of Slovin formula then got 105 sample respondents by using questionnaires that have passed the test of Validity and Reliability. Based on the results of the study obtained Usability, Information Quality, and Service Interaction Quality affect simultaneously to User Satisfaction. Dimensions of Information Quality and Service Interaction Quality partially affect the User Satisfaction. Usability is the only factor that does not affect the User Satisfaction.